Accounting System and Financial Performance Measurements - Zbyněk Halíř (European Financial and Accounting Journal, 2011)
The paper concerns measuring and reporting of financial performance of an enterprise. Currently increasing emphasis is placed on performance measurement and management. Within performance measurement and management in general the role of financial performance is becoming increasingly important. The paper is concerned with measuring and reporting of financial performance of an enterprise primarily from manager's point of view. In its first part it deals primarily with the connection between the performance of an enterprise in general and financial performance. In subsequent part it is about the relation of performance management and management accounting. The next part of the paper is devoted to the dual concept of financial and management accounting and to causes and consequences of the duality. Then it summarizes the most important developmental tendencies of financial performance measurement and management accounting.
Keywords: M41; 650; Performance Measurement; Financial Performance; Management Accounting; Dual Concept